2022
DOI: 10.3389/fneur.2022.940375
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of routine blood parameters in patients with amyotrophic lateral sclerosis and evaluation of a possible correlation with disease progression—a multicenter study

Abstract: ObjectiveAmyotrophic lateral sclerosis (ALS) pathogenesis is still unclear, its course is considerably variable, and prognosis is hard to determine. Despite much research, there is still a lack of easily accessible markers predicting prognosis. We investigated routine blood parameters in ALS patients regarding correlations with disease severity, progression rate, and survival. Additionally, we analyzed disease and patients' characteristics relating to baseline blood parameter levels.MethodsWe analyzed creatine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 91 publications
2
5
0
Order By: Relevance
“…Total protein levels and albumin were initially used as separate variables, possibly accounting for the association observed only for total protein but not albumin. Indeed, after exclusion of total protein levels from the survival analysis, albumin was retained as an independent prognostic factor, consistent with the literature [ 4 , 6 , 22 ], suggesting that it may be a reasonable outcome measure in ALS clinical trials, as recently suggested in the Co-ALS trial [ 24 27 ]. Instead, despite some evidence for the presence of a systemic low-grade inflammation in ALS [ 7 , 28 , 29 ], we did not find an association between CRP and survival, similar to other large cohort studies [ 22 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Total protein levels and albumin were initially used as separate variables, possibly accounting for the association observed only for total protein but not albumin. Indeed, after exclusion of total protein levels from the survival analysis, albumin was retained as an independent prognostic factor, consistent with the literature [ 4 , 6 , 22 ], suggesting that it may be a reasonable outcome measure in ALS clinical trials, as recently suggested in the Co-ALS trial [ 24 27 ]. Instead, despite some evidence for the presence of a systemic low-grade inflammation in ALS [ 7 , 28 , 29 ], we did not find an association between CRP and survival, similar to other large cohort studies [ 22 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 84%
“…Besides its use as a surrogate index of renal function, serum creatinine is also known to reflect muscle mass. In ALS, serum creatinine appears to decrease up to 2 years before diagnosis [ 18 ], with baseline values being consistently positively associated with progression and survival [ 4 , 6 , 19 ]. We confirmed that serum creatinine is a reliable marker of disease severity and mortality in ALS, with a 14% reduction in risk of death observed for each 0.1 mg/dL increase at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, changes in muscle mass are one of the signs of ALS, and they are one of the biochemical parameters that can be assessed in this case is CK. According to the study by Hertel et al, an increased CK level can increase survival time and provide a good interpretation of the ALSFRS-R score [61]; however, a decreased level was indicated in the case of muscle atrophy [34].…”
Section: Discussionmentioning
confidence: 99%
“…The same applies to other well-known ALS markers, such as markers of muscle metabolism (creatine kinase, creatinine, uric acid), and nutritional status (protein, albumin etc.) measured in routine blood workup, even if they correlate with motor neuron loss, disability, and survival [ 119 , 120 , 121 , 122 , 123 ]. Concentrations of the extracellular domain of the common neurotrophin receptor (p75 ECD ) in urine have been reported to reflect motor neuron loss and disease progression as they increase over the course of disease.…”
Section: Molecular Heterogeneitymentioning
confidence: 99%